Prevention of Corruption in the Judicial System (Zien Journal of Social Sciences and Humanities, 2022)
Information on persons reporting corruption offenses, and the fact that the problem of corruption is one of the most pressing problems, it is reported that the prevention and fight against corruption is one of the important steps for the development of the state and society.